Inhibitory Activity of Parsea americana Mill. Peels Extract and Fraction Containing Phenolic Compound Against Staphylococcus aureus ATCC 25923 - Nanik Sulistyani; Lola Angelita; Nurkhasanah Nurkhasanah (Sanata Dharma University, 2022)
Parsea americana Mill. is a natural resource that has been studied for its antibacterial properties. The pulp, peel, and seed of Parsea americana Mill. have potential as an antibacterial agent. This study aimed to determine the inhibitory activity and phenolic content of Parsea americana Mill. peels extract and fraction against Staphylococcus aureus ATCC 25923. Parsea americana Mill. was macerated with 96% ethanol and then fractionated with n-hexane, ethyl acetate, and methanol solvent. Determination of the fraction that has the greatest antibacterial activity against S. aureus was carried out using the Kirby Bauer method. The total phenolic content in the extract and fraction was calculated as gallic acid equivalent (GAE) using the Folin-Ciocalteu method spectrometrically. Antibacterial activity test of the 96% ethanol extract, ethyl acetate fractions, and methanol fractions at a concentration of 10% w/v showed activity with a measurable inhibition zone. On the other hand, the n-hexane fraction showed no inhibition zone. The highest inhibition zone was the ethyl acetate fraction with approximately 8.33 ± 0.58 mm. The ethyl acetate fraction of Parsea americana Mill. resulted in 536.26 ± 14.29 mg GAE/g fraction. The conclusion was that the ethyl acetate fraction had the highest total phenolic content and was the most active fraction in inhibiting the growth of Staphylococcus aureus.